Investigation of photocatalytic-proxone process performance in the degradation of toluene and ethyl benzene from polluted air - Jamal Mehralipour; Ahmad Jonidi Jafari; Mitra Gholami; Ali Esrafili; Majid Kermani (Scientific Reports, 2023)
Abstract In this study, toluene and ethylbenzene were degraded in the photocatalytic-proxone process using BiOI@NH2-MIL125(Ti)/Zeolite nanocomposite. The simultaneous presence of ozone and hydrogen peroxide is known as the proxone process. Nanocomposite Synthesis was carried out using the solvothermal method. Inlet airflow, ozone concentrations, H2O2 concentrations, relative humidity, and initial pollutants concentrations were studied. The nanocomposite was successfully synthesized based on FT-IR, BET, XRD, FESEM, EDS element mapping, UV–Vis spectra and TEM analysis. A flow rate of 0.1 L min−1, 0.3 mg min−1 of ozone, 150 ppm of hydrogen peroxide, 45% relative humidity, and 50 ppmv of pollutants were found to be optimal operating conditions. Both pollutants were degraded in excess of 95% under these conditions. For toluene and ethylbenzene, the synergistic of mechanisms effect coefficients were 1.56 and 1.76, respectively. It remained above 95% efficiency 7 times in the hybrid process and had good stability. Photocatalytic-proxone processes were evaluated for stability over 180 min. The remaining ozone levels in the process was insignificant (0.01 mg min−1). The CO2 and CO production in the photocatalytic-proxone process were 58.4, 5.7 ppm for toluene and 53.7, and 5.5 ppm for ethylbenzene respectively. Oxygen gas promoted and nitrogen gas had an inhibitory effect on the effective removal of pollutants. During the pollutants oxidation, various organic intermediates were identified.